(untitled) - Martin, Terry R. (New York, 2004)
Thoroughly revised and designed to accompany Hole's Human Anatomy and Physiology, this laboratory manual provides increased emphasis on safety and includes several changes that make it more user-friendly.
TT. Sinh lý người và động vật
Keywords: Human anatomy,Giải phẫu người